Excess current/capacitance observation on polymer-fullerene bulk heterojunction, studied through I-V and C/G-V measurements - Kavak, Pelin; Menda, U. Deneb; Parlak, Elif Alturk; Ozdemir, Orhan; Kutlu, Kubilay (ELSEVIER, 2012)
Excess current/capacitance behavior was observed on the Ag:Ca/P3HT:PCBM/PEDOT:PSS/ITO structure and the associated mechanism(s) were identified by performing both dc current-voltage (I-V) and ac capacitance-conductance-voltage (C/G-V) measurements in dark and light exposure, respectively. The excess current/capacitance issue, originated owing to a minority carrier injection, has manifested itself as conductivity modulation in I-V and decrease in capacitance in C-V at a sufficiently large forward bias. Satisfactory analysis in I-V as transport property and C(G)-V as storage feature were carried out on Ag:Ca/P3HT:PCBM/PEDOT:PSS/ITO structure. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Excess current/capacitance; Conductivity modulation; Apparent building voltage; Admittance measurement; MOBILITY; Energy & Fuels; Materials Science; Physics